EDIUSY: the solution of student disengagement / Nur Athirah Sumardi ... [et al.] - Sumardi, Nur Athirah; Mat Halif, Mazuin; Hassan, Narehan; Dzulkalnine, Natasha (Universiti Teknologi MARA, Kedah, 2023)
The past two years, Covid-19 has stroked the world with immediate needs for educators to perform duties and responsibilities from home via the internet and for students to engage in online classes, emphasizing the importance of individuals’ autonomy, efficacy and empowerment. Hence, the concern on student engagement towards lessons has garnered the interest of every educational institution in Malaysia, boiling down to the identification of the solution through EDIUSY. It is a mobile application that was inspired by the VARK learning style model which highlighted the four learning styles of Visual, Auditory, Read or Write and Kinesthetic. This application will benefit its end users specifically tertiary educational institution students, trainers, instructors, or lecturers. Notably, it will enable the students to have comprehensive access to their learning materials, personalized based on their chosen most preferred learning style. Nonetheless, the application is currently focusing on only three learning styles except for kinesthetic as it temporarily concentrates on social science students who are known to be studying theoretically. Later, this will be further expanded to kinesthetic style for technical and pure sciences students who will mostly use hands-on learning materials. Besides, this application also enables personalized sharing of information and materials which will engage and empower the students to be extensively responsible for their studies. With minimal incurred cost, students will feel contented, motivated, happier and able to engage in the classroom without any difficulty. Subsequently, this will create positive student engagement in the teaching and learning environment, which is a win-win situation for both students and educators.